Laparoscopic cholecystectomy in a type Va Mirizzi syndrome patient - Yasin, Fahad; Khan, Wasim Hayat; Butt, Usman Ismat; Umar, Muhammad; Butt, Roshan; Klasra, Abid (Journal of the Pakistan Medical Association, 2022)
Mirizzi syndrome is a rare syndrome, caused by the compression of gall stones which may result in CBD obstruction or fistula formation. It may sometimes present without any prior symptoms. It has been classified into five types by Csendes. Usually open surgical approach is recommended for the condition, especially for Types III-V. We present the case of a patient who presented with right hypochondrial pain and was intra-operatively discovered to have type Va Mirrizi syndrome and was managed successfully laparoscopically. Key words: Mirizzi syndrome, type Va, Laparoscopy.